DESAIN SISTEM INFORMASI REKAM MEDIS DALAM MENUNJANG TATA KELOLA KLINIS REGISTRASI PASIEN RAWAT JALAN DENGAN V-MODEL - Dewi Sri Nurhalimah; Yuda Syahidin; Yuyun Yunengsih (INFOKOM (Informatika & Komputer), 2023)
This study aims to design an information system for outpatient patients using object oriented methods. The research method used in this study is qualitative method with descriptive approach. Data collection techniques used are by direct observation method, interview about patient visit, and literature study. The software development method used is V-Model variation ofwaterfall as well as in its modeling using Unified Modeling Language. From the research conducted found the following problems: (1) The process of making reports of bpjs patient visits is still not optimal; (2) Frequent delays in submitting the final report of patient visits; The suggestions given are: (1) Making the development of Information Systems more effective and efficient; (2) Adding Human Resources and supported by the system so that the report is done quickly and there is no delay in submitting the final report of bpjs patient visit.